Diseño e implementación de un módulo didáctico para el análisis y corrección del factor de potencia para el laboratorio de máquinas eléctricas de la universidad técnica de Cotopaxi. - Muso Gancino, Edwin Gabriel (2019)
Not having a practical didactic module that allows us to visualize the behavior of the electrical variables prompted us to carry out the implementation of a module that aims to graphically visualize the process of correction of the power factor of the loads implemented, the variables that intervene for the correction effect is voltage, current and its phase angle. The ones that are obtained by an energy analyzer that are electrical parameters necessary for the study, by means of a LabView software generates signal processing, which allows the representation of sinewave and vector waves of each one of the current phases as voltage. Using the didactic - practical module the student can analyze and compare the results in a theoretical - practical way and relate them to the power triangle, for the development of the practice the module has a three - phase power supply network of 220 V, in the same is installed inductive and resistive loads that can be combined allowing thus to make the correction of the power factor, the sizing of the capacitors allowed us to make the compensation of reactive energy to the loads implemented in the module thus fulfilling the correction. Realizing the correction scheme of the power factor has allowed the construction of practical didactic module.